Determinant Analysis of Restraint History and Length of Stay (LOS) of Patients with Schizophrenia in Aceh Mental Hospital 2018 - Humaira, Humaira; Saputra, Irwan; Nurjannah, Nurjannah; Usman, Said (Budapest International Research and Critics University, 2020)
Schizophrenia is classified as serious mental illness (SMI) due to its chronicity. Rumah Sakit Jiwa (RSJ) Aceh is the only referral mental hospital in Aceh Province. The number of inpatient visits in 2018 with a diagnosis of schizophrenia is 2,083 (96.12%). The average length of stay is 59.76 days. The purpose of this study was to determine the relationship between history of restraint and the length of stay (LOS) of schizophrenic patients in the Aceh Mental Hospital in 2018. This study uses quantitative method. Secondary data is collected from the medical records of patients returning home in 2018. The study population was all schizophrenic patients who returned in 2018, thus using the total sampling method. The study reveals that history of restraint influences the length of stay (LOS) of schizophrenic patients in Aceh Mental Hospital in 2018. The patients with restraint history was treated longer that the patients without restraint. Restraint exacerbates the clinical symptoms of Schizophrenia and causes physical abnormalities such as wasting in the extremities so that more time is needed in treatment. To avoid the severity of clinical symptoms, extremities deformation and the length of stay, stakeholders need to take strategic steps to eradicate restraint as a method in the handling of people with mental disorders at the community level.